1998
DOI: 10.1046/j.1365-246x.1998.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep structures along the boundary of a collisional belt: attenuation tomography ofPandSwaves in the Greater Caucasus

Abstract: Seismic attenuation (Q−1 ) of P and S waves shows a major discontinuity from the Russian platform to the tectonically active Greater Caucasus. Broadband records show this boundary over paths ≤4° long, as revealed by the decay of amplitude spectra from a digital seismic network flanking the Greater Caucasus. We measure attenuation from individual spectra, using a non‐linear least‐squares procedure to determine an attenuation parameter (t* ) simultaneously with source parameters at frequencies between 1 and 15 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…The dominance of afterslip between 1991 and 1994, and GPS constraints on the upper limit of surface displacements between 1994 and 1996, require a lower crustal viscosity (25 -45 km) of at least 10 18 Pa s. Assuming a temperature gradient of 20 degrees per km, typical wet quartz flow laws [e.g., Gleason and Tullis, 1995] may be ruled out for the lower crust. A somewhat higher effective viscosity would still be consistent with low seismic velocities [Hearn and Ni, 1994] and high attenuation [Kadinski-Cade et al, 1981;Sarker and Abers, 1998;Sandvol et al, 2001] in the thickened, Caucasus lower crust. However, recent modeling studies of young continental collision zones have assumed extremely weak lower crust (for example, 25% of values given by Gleason and Tullis [1995], by Pysklywec et al [2002]) to decouple the mantle lithosphere from the upper crust.…”
Section: Discussionmentioning
confidence: 74%
“…The dominance of afterslip between 1991 and 1994, and GPS constraints on the upper limit of surface displacements between 1994 and 1996, require a lower crustal viscosity (25 -45 km) of at least 10 18 Pa s. Assuming a temperature gradient of 20 degrees per km, typical wet quartz flow laws [e.g., Gleason and Tullis, 1995] may be ruled out for the lower crust. A somewhat higher effective viscosity would still be consistent with low seismic velocities [Hearn and Ni, 1994] and high attenuation [Kadinski-Cade et al, 1981;Sarker and Abers, 1998;Sandvol et al, 2001] in the thickened, Caucasus lower crust. However, recent modeling studies of young continental collision zones have assumed extremely weak lower crust (for example, 25% of values given by Gleason and Tullis [1995], by Pysklywec et al [2002]) to decouple the mantle lithosphere from the upper crust.…”
Section: Discussionmentioning
confidence: 74%
“…For regional paths, spectral fall-off of body waves can be inverted for attenuation along with source parameters in a parametric scheme (e.g., LEES and LINDLEY, 1994;SARKER and ABERS, 1998). The spectral fitting scheme, based on the approach of HOUGH et al (1988) and BOATWRIGHT (1978), fits a three-parameter source model H( f ) to observed amplitude spectra, where…”
Section: Attenuation Measurement Methodsmentioning
confidence: 99%
“…These different approaches and descriptions of attenuation do not always lead to the same results. For example, in the Caucasus, the Q s values measured from spectral fall-off (SARKER and ABERS, 1998) are 3 times larger than Q coda measured from lapse time decay (RAUTIAN et al, 1979). Large differences are also seen in southern California between the coda Q values of 200 of SINGH and HERRMANN (1983) and body wave Q values of 800 and 1025, determined by FRANKEL et al (1990) and HOUGH et al (1988), respectively.…”
Section: Introductionmentioning
confidence: 94%
“…The t* measurements are inverted for spatial variations in 1/Q following the velocity inversion scheme of Roecker [1993], as modified by Sarker and Abers [1998a]. In a continuous medium, t* measurements should be related to spa- To trace rays, we assume a simple, one-dimensional velocity for the entire region with constant velocity layers ( The a priori uncertainties in the model correspond to 100% uncertainty in the a priori model, a conservative but defensible assumption that may contribute to unreasonably large uncertainties.…”
Section: Inversion Of T* For 1/qmentioning
confidence: 99%